Peningkatan Sumber Daya Manusia Indonesia di Era MEA - Setiawan, Bagus (Jurusan PIPS FKIP UMMY Solok, 2017)
The era of globalization that is both certain and inevitable for the people of the world must be addressed in an appropriate manner. Physical development as well as human resources becomes the main points to be improved for us to be able to face and compete in the global era. Regional ASIA MEA era is in sight is clear we face, improving the quality of the local community must be well prepared for the Indonesian people as a whole. The education level or standard of education needs to be improved in addition to the constantly working to improve the skills of self that is needed in the MEA era like today. Not just a matter of knowledge and skills that can be acquired through formal education, but also the mental problems, faith and character should also be improved in order to maintain the direction of development of Indonesia that is more stable in the face of MEA era.